The effective direct resolution procedure for the chiral drug bevantolol hydrochloride. Issue 9 (1st June 2016) - Bredikhina, Zemfira A.; Antonovich, Olga A.; Zakharychev, Dmitry V.; Bredikhin, Alexander A.
Graphical abstract: Abstract: The solubility of the chiral drug bevantolol hydrochloride 1 in water and the azeotropic mixture ethanol–water has been investigated. It was found that rac -1 meets the requirements of Meyerhoffer's rule, so it was possible to reduce the ternary diagram, describing the solubility of1, to a pseudo binary form, which facilitates the analysis of crystallization processes caused by temperature changes. On this basis, the effective and robust resolution procedure of racemic bevantolol hydrochloride by a preferential crystallization approach has been realized successfully. Abstract : ( R )-1-[[2-(3, 4-Dimethoxyphenyl)ethyl]amino]-3-(3-methylphenoxy)-2-propanol: C20 H28 ClNO4 Ee  = 99.8% ( ee from HPLC) [ α ]D 20  = +19.3 ( c 1.1, EtOH) Initial source of chirality: resolution of racemic 1-[[2-(3, 4-dimethoxyphenyl)ethyl]amino]-3-(3-methylphenoxy)-2-propanol by preferential crystallization Absolute configuration: ( R ) Abstract : ( R )-1, 2-Epoxy-3-(2-methylyphenoxy)propane: C10 H12 O2 [ α ]D 20  = −12.9 ( c 1.0, MeOH) Initial source of chirality: ( S )-epichlorohydrin Absolute configuration: ( R )